2013
DOI: 10.4196/kjpp.2013.17.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Induced Cardioprotection against Myocardial Ischemia in Guinea Pig

Abstract: This study was designed to evaluate the protective effect of Korean red ginseng (KRG) against ischemia/reperfusion (I/R) injury in isolated guinea pig heart. KRG has been shown to possess various ginsenosides, which are the major components of Panax ginseng. These components are known naturally occurring compounds with beneficial effects and free radical scavenging activity. The heart was induced to ischemia for 60 min, followed by 120 min reperfusion. The hearts were randomly allocated into five groups (n=8 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Red ginseng extract (250e500 mg/kg/day per os for 7e9 days) improved ventricular hemodynamic function parameters, reduced ST segment and QRS complex intervals and increased antioxidant myocardial levels in both pigs and rats with isoproterenol-induced cardiac injury (Lim et al, 2013a(Lim et al, , 2014. Similarly, Korean red ginseng (250e500 mg/kg/day per os for 14 days) suppressed both lactate dehydrogenase and creatine kinase-MB fraction and cardiac troponin I and reduced oxidative stress-induced damage in guinea pigs with I/R injury; as a consequence, aortic flow, coronary flow, cardiac output and left ventricular systolic pressure increased (Lim et al, 2013b). A P. quinquefolius extract (50 mg/kg/day per os for 7 days) decreased infarct size and myocardial apoptosis in mice with I/R damage via activation of eNOS (Wu et al, 2011b).…”
Section: Cardiovascular Systemmentioning
confidence: 97%
“…Red ginseng extract (250e500 mg/kg/day per os for 7e9 days) improved ventricular hemodynamic function parameters, reduced ST segment and QRS complex intervals and increased antioxidant myocardial levels in both pigs and rats with isoproterenol-induced cardiac injury (Lim et al, 2013a(Lim et al, , 2014. Similarly, Korean red ginseng (250e500 mg/kg/day per os for 14 days) suppressed both lactate dehydrogenase and creatine kinase-MB fraction and cardiac troponin I and reduced oxidative stress-induced damage in guinea pigs with I/R injury; as a consequence, aortic flow, coronary flow, cardiac output and left ventricular systolic pressure increased (Lim et al, 2013b). A P. quinquefolius extract (50 mg/kg/day per os for 7 days) decreased infarct size and myocardial apoptosis in mice with I/R damage via activation of eNOS (Wu et al, 2011b).…”
Section: Cardiovascular Systemmentioning
confidence: 97%
“…MIR injury, accompanied by contractile dysfunction and cellular damage, is still one of the primary causes of death (Lim et al 2013). The ischemic heart exhibits decreased oxidative metabolism of both FFAs and glucose, which increases the D r a f t AMP/ATP ratio.…”
Section: R a F Tmentioning
confidence: 99%
“…It is variously used to treat specific diseases, as traditional medicine in East Asia. And numerous studies showed that P. ginseng has protective effects against degenerative and aging diseases, such as neurodegenerative diseases (Cho, 2012), anti lipid accumulation (Yang et al, 2014), diabetic nephropathy (Quan et al, 2013), osteoporosis (Siddiqi et al, 2013), regulating the inflammatory response (Kim et al, 2015), ischemia, oxidative stress (Lim et al, 2013), and potential chemopreventive effects (Kim et al, 2013, Sharma and Goyal, 2015).…”
Section: Introductionmentioning
confidence: 99%